2017
DOI: 10.1111/jgh.13495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphism and hepatic expression of duodenal cytochrome b in chronic hepatitis C

Abstract: These results implicate CYBRD1 involvement in iron homeostasis in CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… 24 Based on extensive references, CYBRD1 mainly contributed to the transportation of glucose and other sugars, 25 metal ions, bile salts, and organic acids, as well as the absorption of mineral. 26 CYBRD1 has been proved to be involved in the development of HFE hemochromatosis, 27 chronic hepatitis C, 28 and alcoholic liver disease. 29 Additionally, Lemler DJ et al demonstrated that DCYTB was a potential biomarker for breast cancer and exerted its functional effect through an iron‐independent manner.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Based on extensive references, CYBRD1 mainly contributed to the transportation of glucose and other sugars, 25 metal ions, bile salts, and organic acids, as well as the absorption of mineral. 26 CYBRD1 has been proved to be involved in the development of HFE hemochromatosis, 27 chronic hepatitis C, 28 and alcoholic liver disease. 29 Additionally, Lemler DJ et al demonstrated that DCYTB was a potential biomarker for breast cancer and exerted its functional effect through an iron‐independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The CYBRD1 rs884409 polymorphism associates with variation in serum transferrin saturation and ferritin concentration in patients with HFE C282Y mutation and the mutated allele reduces CYBRD1 promoter activity by 30% [ 39 , 40 ]. CYBRD1 rs884409 was found previously to associate with liver inflammation, liver enzymes and bilirubin in CHC patients [ 20 ]. In our study this SNP was linked with liver inflammation grade ( Table S4 ) and liver steatosis ( Table 1 , Table S5 ) as well as serum liver enzymes, bilirubin, and iron concentration ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…All patients were treated in the Department of Infectious Diseases, Medical University of Gdansk, Poland. Selected patients were analyzed in previous studies [ 18 , 20 ]. The baseline characteristics of patients are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%